Avaliação da obliteração de túbulos dentinários pelo uso de dentifrícios com agentes dessensibilizantes: estudo em ratos - Pinto, Shelon Cristina Souza (2008)
The aim of this study was to evaluate the physico-chemical characteristics of dentifrices with desensitizing agents as well as their capability for obliterate dentinal tubules. In vitro study: Physical and chemical properties were analyzed using the loss desiccation test, pH analysis, microbiologic test, scanning electronic microscopy (SEM) and energy dispersive x ray (EDX). The dentifrices were: Sensodyne original® (GSO); Colgate sensitive branqueador® (GCS) and Sensodyne Proteção Total® (GSPT). In vivo study: Forty rats with 90 days and weighing 200-270 grams were divided into the following groups: GSO: (n=10) strontium chloride (Sensodyne original®); GCS- (n=10) potassium citrate (Colgate sensitive whitening®), GSPT- (n=10) potassium nitrate (Sensodyne Protector Total®) and GAD- (n=10) distilled water (Control). Upper and lower incisors had dentinal tubules exposed with cervical abrasion in superficial (0.2 mm) and deep dentin (0.4mm). Smear layer was removed by actively etched with a 24% EDTA gel per 3 minutes, after samples were toothbrushed (15 movements) daily, for 4 days. After each treatment, 5 μl of Evans blue dye solution was applied to the teeth. The samples were prepared to dentin permeability, scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX) analysis. Physico-chemical dentifrices characterization results: GSO (64.34±0.85) showing a higher solid residue and GCS (40.08±1.71) the lower. Basic pH were observed (GSO- 7.81±0.011, GCS- 8.00±0.043, GSPT- 8.36±0.055). Dentifrices not showed bacterial growth or fungal. SEM analysis showed inorganic particles. Exception fluoride, desensitizing agents’ chemicals elements were detected by EDX analysis. In vivo study: There was significant difference among test groups and control for dentin permeability (p<0.001). Superficial and deep dentin had similar dentinal tubules number per mm2, statistical difference was observed in deep dentin between GSO and GAD (p>0.05). The dentinal tubules area and diameter were similar in test groups, but these had a significant difference (p<0.001) with control group (higher area and diameter). GSO, GCS e GSPT (superficial and deep dentin) showed open and partial obliterated tubules. Most opened tubules were observed on GAD. EDX showed a low quantity of desensitizing agents’ elements. According to the methodology used was possible to conclude that the dentifrices had different physico-chemical characteristics, suggesting different abrasive pattern. All agents tested were able to decrease dentine permeability and partial obliteration of dentinal tubules.